Intraoperative Navigation einer Distraktionsverletzung der BWS bei schwersten skoliotischen Veränderungen - Schramm, Simon; Groh, Johannes; Krause, Johannes; Perl, Mario (Die Unfallchirurgie, 2024)
The case of a 43-year-old male patient is described, who suffered several injuries due to a traffic accident, including a distraction injury to the thoracic spine. A specific feature of this case was the existing spondylodesis with material fracture and secondary loss of reduction. Due to this, the guidewires of the pedicle screws were placed in a navigation pattern in the absence of adjustable pedicles and an abnormal screw corridor. This guarantees an optimal positioning with associated patient safety.
CRIS-Team Scopus Importer:2024-05-10
Keywords: 3D imaging; Distraction injury; Multiple trauma; Navigation; Spinal trauma